2009
DOI: 10.1155/2009/758108
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review on Dynamics of a Cracked Rotor

Abstract: Fatigue crack is an important rotor fault, which can lead to catastrophic failure if undetected properly and in time. Study and Investigation of dynamics of cracked shafts are continuing since last four decades. Some review papers were also published during this period. The aim of this paper is to present a review on recent studies and investigations done on cracked rotor. It is not the intention of the authors to provide all literatures related with the cracked rotor. However, the main emphasis is to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 61 publications
0
31
0
1
Order By: Relevance
“…Thus the influence of static toque should be considered in crack detection. (2) Owing to the coupling of bending and torsional vibration of slant cracked rotor, the torsional excitation frequency and the combined frequency components of rotating frequency will appear in transverse vibration response of the rotor under the action of periodic torsional excitation, and the higher the exciting amplitude is, the larger the combined frequency components are. (3) As the transmitted static torque will make the crack in normally open state and change the nonlinearity of the system, the crack detection can be carried out by loading and unloading the power transmission, and comparing the vibration characteristics before and after load change; furthermore, the load should be used as an important monitoring parameter in condition monitoring on rotor systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the influence of static toque should be considered in crack detection. (2) Owing to the coupling of bending and torsional vibration of slant cracked rotor, the torsional excitation frequency and the combined frequency components of rotating frequency will appear in transverse vibration response of the rotor under the action of periodic torsional excitation, and the higher the exciting amplitude is, the larger the combined frequency components are. (3) As the transmitted static torque will make the crack in normally open state and change the nonlinearity of the system, the crack detection can be carried out by loading and unloading the power transmission, and comparing the vibration characteristics before and after load change; furthermore, the load should be used as an important monitoring parameter in condition monitoring on rotor systems.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is significant for crack detection to investigate the influence of torsional excitation on the dynamic characteristic of the power transmission rotor with slant breathing crack. Though much research has been carried out on the cracked rotor dynamics [1][2][3][4] , most of which aim at rotors with transverse cracks and assume the gravity dominant, yet the slant crack is seldom studied at present. However, the cracks in rotors are often slant cracks due to transmitted torque.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in the literature that the presence of a crack introduces additional flexibility to the shaft, which reduces its overall stiffness and generates complex orbits and super-harmonic frequency components [15,16]. The dynamic analysis of cracked rotor systems has been intensively studied by many researchers [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the work of Tada et al (1973), many researchers have performed the vibration analysis of the cracked structures such as thin walled tubes during the last five decades. Recently, some reviews on vibration of cracked structures were reported by Dimarogonas (1996) and Kumar et al (2010). In some researches the crack has been simulated by a local reduced section or stiffness of the structure around the crack (Sinha, Friswell et al 2002).…”
Section: Introductionmentioning
confidence: 99%